Novel Algal Polysaccharides from Marine Source: Porphyran - Bhatia, S.; Sharma, A.; Sharma, K.; Kavale, M.; Chaugule, B. B.; Dhalwal, K.; Namdeo, Ajay G.; Mahadik, K. R. (Pharmacognosy Reviews)
Porphyran is a sulfated polysaccharide derived from Porphyra sp. It comprises of sulfate ester and 3, 6-anhydrogalactose whose arrangement is similar to agarose. Porphyran has enormous reported activities. It has potential pharmaceutical, medicinal and research applications. Porphyran a promising product is useful to produce antiallergic, anticancer, antioxidant, antitumour, antiviral, immunostimulant, antifatigue, metallic adsorption ability, improvement of intestinal flora, antibacterial, anticoagulant, antiviral, microphage promotion action, hepatoprotective agent, antihyperlipidemic, hypocholesterolemic, hypoglycemic, hypotensive, antiulcer and prebiotic activity. Despite of all this it is also used as gelling agent. Currently porphyran availabilty in the market is not known because of several problems such as its high molecular weight, high viscosity and availability of Porphyra. So it is very necessary to know about basic facts regarding Porphyra sp. before obtaining any novel compound from it.
Keywords: Porphyran; Nori; Porphyra; Sulfated polysaccharides; Seaweeds; galactans